UNIVERSAL BANKING DITINJAU DARI PERSPEKTIF NILAI PEMEGANG SAHAM - Ardhiputra, Hafiz (Jurnal Akuntansi AKUNESA, 2014)
Universal banking system is considered as a modern banking system in the world. This system makes bank can provide financial services practically. The concept of universal banking can give benefit in economic side and improve bank performance in some countries. As a bank with wider scope, there is main purpose by bank, which creates a positive perspective, including shareholder?s value creation. The concept of universal banking also has a dark side, which impact negatively in application of those concept and also cause moral hazard due to asymetric information. Bank needs a good risk management, strong regulation and innovative strategy to create a positive perspective for banks that using concept of universal banking. Keywords : Universal banking, benefits, performance, shareholder